2013
DOI: 10.4141/cjas2013-073
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Ruminal pH profile and feeding behaviour of feedlot cattle transitioning from a high-forage to a high-concentrate diet

Abstract: Holtshausen, L., Schwartzkopf-Genswein, K. S. and Beauchemin, K. A. 2013. Short Communication: Ruminal pH profile and feeding behaviour of feedlot cattle transitioning from a high-forage to a high-concentrate diet. Can. J. Anim. Sci. 93: 529–533. Sixteen ruminally cannulated cattle (384±33.9 kg) were transitioned from a high-forage to a finishing diet over 21 d using three steps (+15% concentrate DM wk−1). Following the initiation of each transition step, mean daily ruminal pH declined and DM intake, meal size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…Whereas, pH, NH 3 -N, and VFA decreased linearly with increased concentrate levels. The decline in rumen pH was associated with slow ammonia absorption in rumen and the small changes in rumen pH can have a marked influence on ammonia absorption from the rumen, through its effect on unionized ammonia concentrations have also been reported [21,22]. Results of the study revealed that rumen ammonia was either rapidly absorbed or incorporated in the microbial mass, thus did not corroborate with total-N-concentration in the rumen fluid.…”
Section: Discussionmentioning
confidence: 84%
“…Whereas, pH, NH 3 -N, and VFA decreased linearly with increased concentrate levels. The decline in rumen pH was associated with slow ammonia absorption in rumen and the small changes in rumen pH can have a marked influence on ammonia absorption from the rumen, through its effect on unionized ammonia concentrations have also been reported [21,22]. Results of the study revealed that rumen ammonia was either rapidly absorbed or incorporated in the microbial mass, thus did not corroborate with total-N-concentration in the rumen fluid.…”
Section: Discussionmentioning
confidence: 84%
“…However, none of those studies incorporated long-term measurement of ruminal pH in the same cattle. In the current study, we observed that the DUR was, on average, 4.1, 12.5, 78.8, and 194 min/d during BKGD, TRAN, FIN1, and FIN2, indicating that the severity of ruminal acidosis may be overestimated in short-term studies or in studies when cattle are group housed but feeding behavior is constrained to a limited amount of feed bunk space, as is the case for studies using feed intake monitoring systems (Schwartzkopf-Genswein et al, 1999;Mendes et al, 2011;Holtshausen et al, 2013). Nonetheless, these results suggest that the reduction in ruminal pH for groupfed cattle is not as severe as would have been predicted by extrapolating results from short-term studies.…”
Section: Incidence Prevalence and Severity Of Ruminal Acidosismentioning
confidence: 79%
“…Novel results from the current study indicate that the incidence and prevalence rates for ruminal acidosis were 0.1, 0.3, 6.7, and 14.9 and 0.7, 1.7, 15.4, and 37.8%, respectively. While incidence and prevalence rates have not been reported previously, past studies using individually fed cattle report values for DUR between 233 and 1,251 min/d below pH 5.6 (Bevans et al, 2005;Vander Pol et al, 2009;Crawford et al, 2008) and between 340 and 601 min/d (Meyer et al, 2009;Wierenga et al, 2010) once fed finishing diets or during the last step up of a diet transition (Holtshausen et al, 2013). However, none of those studies incorporated long-term measurement of ruminal pH in the same cattle.…”
Section: Incidence Prevalence and Severity Of Ruminal Acidosismentioning
confidence: 95%
See 2 more Smart Citations